On beauty, scholarship, and function: The lessons from, and importance of, legal history in the development of the law of marine insurance: [Review of] Marine Insurance: A legal history by Rob Merkin - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 2023)
A few words of explanation at the outset are perhaps necessary – if nothing else than to explain the apparently cryptic title of this review essay. What in fact began as a somewhat straightforward review of a book on the history of marine insurance took a wholly unexpected turn and morphed into a general essay on the beauty, scholarship and function of legal history as viewed through the lenses of marine insurance. Indeed, in addition to being a magisterial two-volume history of the law of marine insurance, the present work demonstrates – in the most vividly possible way – at least three fundamental aspects (or, more accurately, benefits) of legal history as a whole.